Braconidae (Hymenoptera) in the collection of the Institute of Zoology, NAS of Azerbaijan Republic Part III. Subfamilies Helconinae, Brachistinae, Euphorinae, Macrocentrinae (Hymenoptera). - Abdinbekova, Arifa; Huseynova, Ellada; Kerimova, Ilhama (Contributions to Entomology = Beiträge zur Entomologie, 2013)
The paper gives some faunistic records of the braconids from genera Cenocoelius, Diospilus, Taphaeus belonging to subfamily Helconinae, from genera Eubazus, Polydegmon, Triaspis, Schizoprymnus belonging to subfamily Brachistinae, from genera Meteorus, Zele, Chrysopophthorus, Aridelus, Blacus, Dinocampus, Microctonus, Pigostolus, Centistes, Ancylocentrus, Leiphron, Peristenus, Wesmaelia, Syntretus belonging to subfamily Euphorinae and from genus Macrocentrus belongin to subfamily Macrocentrinae from the collection of the institute of Zoology of the National Academy of Sciences of Azerbaijan located in Baku. For each taxon localities in Azerbaijan, distribution and hosts remarks are given. 27 species from the collection is located in the ZIN (Zoological Institute of the RAS) so we have not presented information about them. This concerns: Centris (Ancylocentrus) subculcatus (Thomson, 1895), Allurus muricatus (Haliday, 1833), Eubazus (Aliolus) kusarensis (Abdinbekova,1969), Eubazus (Allodorus) semirugosus (Nees, 1816), Chrysopophthorus hungaricus (Kiss, 1927), Ecclitura primoris Kokuyev, 1902, Eubazus (Eubazus) pallipes Nees, 1816, E. (Brachistes) rufithorax (Abdinbekova, 1969), E. (Brachistes) minutus (Ratzeburg, 1848), E. (Brachistes) talitzkii Tobias, 1976, Schizoprymnus crassiceps (Thomson, 1891), Schizoprymnus elongatus (Szépligeti, 1898), Sch. subangustatus Tobias 1976, Sch. ambiguus (Nees, 1816), Sch. globosus (Szépligeti, 1898), Helcon tardator Nees, 1814, Homolobus infimator (Lyle, 1914), Homolobus annulicornis (Nees, 1834), Leiophron palidistigma Curtis, 1833, Meteorus heliophilus Fischer, 1970, Meteorus cespitator (Thunberg, 1822), Perilitus (Townesilitus) bicolor (Wesmael 1835), Perilitus (Townesilitus) breviradialis (Tobias, 1976), Macrocentrus brevicaudifer Van Achterberg 1979, Macrocentrus flavus Snellen van Vollenhoven, 1878, Macrocentrus thoracicus (Nees, 1812), Macrocentrus marginatus (Nees, 1811).